2017
DOI: 10.1002/col.22168
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and emotion are indifferent to ambient color

Abstract: Folklore has it that ambient color has the power to relax or arouse the observer and enhance performance when executing cognitive tasks. We picked a number of commercially available colors that allegedly have the power to alter cognitive performance and the emotional state, and exposed subjects to them while solving a battery of cognitive tasks. The colors were "Cool Down Pink", which is said to produce relaxing effects and reduce effort, "Energy Red", allegedly enhancing performance via increased arousal, "Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
(88 reference statements)
3
22
0
3
Order By: Relevance
“…Our finding (that there is a positive correlation between the number of excellent performers and relative leftward PFC activity) is in accordance with previous research [ 42 ] which concluded that during the VFT, subjects with excellent task performance showed a left-dominated dorsolateral frontal asymmetry, while moderate performers showed a right-dominated frontopolar asymmetry [ 42 ]. Moreover, slightly better VFT performance with red as compared to blue light exposure is in line with many color and colored light studies which have proposed that red improves task performance in comparison with other colors [ 73 , 74 , 75 , 76 , 77 ]. In particular, red enhances the performance for “overlearned motor”, “proofreading”, “target shooting”, and “basic strength” tasks [ 76 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our finding (that there is a positive correlation between the number of excellent performers and relative leftward PFC activity) is in accordance with previous research [ 42 ] which concluded that during the VFT, subjects with excellent task performance showed a left-dominated dorsolateral frontal asymmetry, while moderate performers showed a right-dominated frontopolar asymmetry [ 42 ]. Moreover, slightly better VFT performance with red as compared to blue light exposure is in line with many color and colored light studies which have proposed that red improves task performance in comparison with other colors [ 73 , 74 , 75 , 76 , 77 ]. In particular, red enhances the performance for “overlearned motor”, “proofreading”, “target shooting”, and “basic strength” tasks [ 76 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 86%
“…Apart from that, the good news for the designer is that the choice of hue and saturation can be made (almost) entirely on aesthetic grounds, because their effect on the perceived height of an interior space is absent or small. Following these considerations, hue and saturation can be applied in order to obtain a further design goal, such as an intended emotional effect of the paint (e.g., Acking & Küller, 1972;Franz, 2006;Odabasioglu & Olguntürk, 2015;Wilms & Oberfeld, 2017;Yildirim, Hidayetoglu, & Capanoglu, 2011; but see von Castell, Stelzmann, Oberfeld, Welsch, & Hecht, 2018). Note that this does not rule out potential interactions of surface color with other factors that likely do influence the perceived layout of interior spaces, such as furniture and decor.…”
Section: Discussionmentioning
confidence: 99%
“…To display interior color with precision, a majority of relevant studies manipulated color variables of interest while keeping other confounding factors constant in physical spaces (e.g., laboratory and real‐life spaces). For example, a significant portion of studies represented interior colors using simple methods (e.g., a colored wall, printed colored image, or colored light) in a laboratory space (Al‐Ayash et al, 2016; Küller et al, 2009; Kwallek, Soon, Woodson, & Alexander, 2005; Öztürk, Yilmazer, & Ural, 2012; von Castell, Stelzmann, Oberfeld, Welsch, & Hecht, 2018). However, such color manipulations are difficult to control with exactness, and it is therefore possible that the user's perceptual experience may be altered.…”
Section: Literature Reviewmentioning
confidence: 99%